Penerapan Kurikulum Merdeka Pada Pendidikan Anak Usia Dini di Taman Kanak-kanak Telkom School Padang - Rasisah Nannela; Zulminiati Zulminiati (Ar-Raihanah: Jurnal Pendidikan Islam Anak Usia Dini, 2023)
The background of this research is whether the implementation of the independent curriculum has been implemented well in early childhood education. This can be seen how the teacher designs planning, implementation and assessment/evaluation during learning. This study aims to determine the implementation of the independent curriculum in early childhood education at Telkom School Padang Kindergarten. This research approach uses descriptive research methods with a qualitative type of approach, where the data from this research are in the form of sentences. The technique of collecting data in this study was by means of observation, interviews and documentation with the research subject of class B3 teachers at Telkom School Padang Kindergarten as well as research informants from school principals, teacher boards and early childhood at Telkom School Padang Kindergarten. The results of the study show that lesson planning, learning implementation and learning evaluation are important things to prepare and implement properly in implementing the independent curriculum in early childhood education